Development of spectrophotometric determination method for Au(III) and Ag(I) - ERDOĞAN, GÜLBİN (MARMARA UNIV, FAC PHARMACY, 2017)
In this research, a potentiometric and spectrophotometric method was developed to determine Ag(I) and Au(III) based on their reaction with m and p-phenylenediamine. As a result reactions between Ag(I) and Au(III) and m-and p-phenylenediamine mixtures was revealed that, there is an oxidation by means of complexation via oxidation, a diazo compound occured from amines and Ag(I) was reducted to elementel form, Au(III) was reducted to Au(I). Also the formation conditions of the reactions of these metals with amines were investigated, the pH range that the reactions took place, time needed for the formation of the reactions and the mol ratios needed for the complete reaction of the metals with amines. Mole ratios were determined as follows: Ag(I) / (m+p) phenylenediamine= 1; Au(III) / (m+p) phenylenediamine= 1/2
Keywords: Spectrophotometer; potentiometer; m- ve p-phenylenediamine; Ag(I) and Au(III); GOLD(III); GOLD